THE ROLE OF ISLAMIC EDUCATION IN CULTURAL TRANSFORMATION IN THE TOBA BATAK MUSLIM COMMUNITY - Harfiani, Rizka; Munir Aritonang, Abdul Rahman; Fitri Tanjung, Ellisa (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of preparing this proceeding article is to analyze the role of Islamic education in cultural transformation in the Toba Batak Muslim community, namely in the Sirihit-rihit community, Setia Village, Pahae Jae District, North Tapanuli. This research method uses a social constructivism paradigm, with a qualitative approach, and is an ethnographic research type. Data analysis used domain analysis and data validity test used the triangulation method, both techniques and sources. The local culture studied is the culture practiced by the Toba Batak people for generations, namely the wedding tradition (Parbagason), the tradition of entering a new house (Mamasuki Jabu), the tradition of thanksgiving for the birth of children (Mangharoani), and the tradition of death (Mangapuli). The findings of this study indicate that the implementation of local culture in the Sirihit-rihit community has undergone a cultural transformation, be it changes in tradition, reduction or addition of ritual events, and the emergence of new traditions as a cultural innovation, to changes in the meaning of ritual symbols, which occurred because of the inclusion of Islamic teachings in society.